Malignant tumors of the appendix.: Surgical patterns - Estrugo, Roberto; Bowley, Hilmer; Acosta, Giselle; Chevalier, Nelma; Iraola, María L (Cirugía del Uruguay, 1985)
Description o a series of 10 malignan! tumors of the appendix - 8 carcinoid tumors and 2 adenocarcinomes. Considerations on pathological and clinical aspects and, basically, on operative tactics through a bibliographic review of the subject. The surgical action will have two options: !he appendicectomy and right hemicolectomy, the selection of which will be made on the basis of macro and microscopy intra and postoperative. Fi• nally, poor pronostic conditions of adenocarcinomas is pointed out, in contras! with that of carcinoid neoplasms and cystadenomas of this topography.